Plan Choice and Changes in Access to Care over Time for SSI-Eligible Children with Disabilities - Pamela N. Roberto; Jean M. Mitchell; Darrell J. Gaskin (SAGE Publishing, 2005)
This paper analyzes how voluntary enrollment in the fee-for-service (FFS) system versus a partially capitated managed care plan affects changes in access to care over time for special needs children who receive Supplemental Security Income (SSI) due to a disability. Four indicators of access are evaluated, including specialty care, hospital care, emergency care, and access to a regular doctor. We employ the Heckman two-step estimation procedure to correct for the potential nonrandom selection bias linked to plan choice. The findings show that relative to their counterparts in the partially capitated managed care plan, SSI children enrolled in the FFS plan are significantly more likely to encounter an access problem during either of the time periods studied. Similarly, FFS enrollees are significantly more likely than partially capitated managed care participants to experience persistent access problems across three of the four dimensions of care. Possible explanations for the deterioration in access associated with FFS include the lack of case management services, lower reimbursement relative to the partially capitated managed care plan, and provider availability.